2019
DOI: 10.5312/wjo.v10.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Damage control orthopaedics: State of the art

Abstract: Damage control orthopaedics (DCO) originally consisted of the provisional immobilisation of long bone - mainly femur - fractures in order to achieve the advantages of early treatment and to minimise the risk of complications, such as major pain, fat embolism, clotting, pathological inflammatory response, severe haemorrhage triggering the lethal triad, and the traumatic effects of major surgery on a patient who is already traumatised (the “second hit” effect). In recent years, new locations have been added to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 128 publications
(148 reference statements)
0
18
0
1
Order By: Relevance
“…Additionally, certain aspects of initial injury types were observed to imply a special risk for secondary complications including SIRS, MOF, sepsis, or ARDS. With DCO treatment, the survival and the rate of complications was improved (170)(171)(172)(173)(174)(175). This observation was supported by a prospective randomized study that showed a reduction of acult lung injuries in borderline patients (12), two supportive trauma registry analyses from the NTDB and Tr_DGU, and a matched pair analysis (162).As a result damage control orthopedics appears to represent a feasible option for patients at special risk and has been applied worldwide, independent of trauma center, geographic or treatment differences (174,(176)(177)(178)(179)(180)(181).…”
Section: Damage Control Orthopaedics (Dco)mentioning
confidence: 99%
“…Additionally, certain aspects of initial injury types were observed to imply a special risk for secondary complications including SIRS, MOF, sepsis, or ARDS. With DCO treatment, the survival and the rate of complications was improved (170)(171)(172)(173)(174)(175). This observation was supported by a prospective randomized study that showed a reduction of acult lung injuries in borderline patients (12), two supportive trauma registry analyses from the NTDB and Tr_DGU, and a matched pair analysis (162).As a result damage control orthopedics appears to represent a feasible option for patients at special risk and has been applied worldwide, independent of trauma center, geographic or treatment differences (174,(176)(177)(178)(179)(180)(181).…”
Section: Damage Control Orthopaedics (Dco)mentioning
confidence: 99%
“…Twenty-two patients with multiple fractures at other anatomical sites were staged, treated, and xed according to the Damage control orthopedics (DCO) surgical strategy [18]. Another 9 patients combined with rib fractures received conservative treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, some studies also reported the onset of FES prior to surgery, even within 24 h after the initial trauma [ 19 , 82 , 83 ]. We hypothesize that the inclusion of endpoints of resuscitation [ 84 ], application of lactate clearance [ 85 ], and revised criteria for patients at special risk (borderline patients) have played a role [ 86 ]. We are aware that FES will occur in some patients irrespective of the timing of the definitive treatment [ 1 ].…”
Section: Discussionmentioning
confidence: 99%